Recurrent breast cancer in the subpectoral space after implant reconstruction. Issue 5 (20th November 2013) - Pitcher, Austin A.; Chao, Jerry W.; Varma, Sonal; Swistel, Alexander J.; Otterburn, David M.
<x xml:space="preserve">Abstract</x> Breast reconstruction after mastectomy is most commonly performed with a prosthetic implant placed beneath the pectoralis major. Recurrence may rarely be identified in the subpectoral space where the implant was placed. We report a case of recurrent breast cancer after implant‐based reconstruction with isolated subpectoral recurrence discovered 5 years later during secondary revision of her reconstructed breast. J. Surg. Oncol. 2014 109:431–433. © 2013 Wiley Periodicals, Inc.